PENERAPAN ANGGARAN BERBASIS KINERJA DALAM PENGELOLAAN KEUANGAN NEGARA UNTUK MEWUJUDKAN GOOD GOVERNANCE - Henny Juliani (Faculty of Law, Universitas Diponegoro, 2010)
Process of state financial management is professionally referred to public sector financial management, transparent, and accountable. Budgeting is based on performance-based budgeting system requires the state ministries/institutions/regional work units to be able to perform measurements on the performance of each agency using the performance measurement elements, so that the delivery of objectives and resuits of these can be felt by the people. This can be accomplished by using the principles of good governance.